2012
DOI: 10.1094/pdis-08-11-0683-re
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Potential of Polyclonal Antibodies Against Bacterially Expressed Recombinant Coat Protein of Alfalfa mosaic virus

Abstract: Khatabi, B., He, B., and Hajimorad, M. R. 2012. Diagnostic potential of polycional antibodies against bacteriaily expressed recombinant coat protein of Alfalfa mosaic virus. Plant Dis. 96; 1352-1357.Alfalfa mosaic virus (AMV), a pathogen of a wide range of plant species, including Glycine max (soybean), is poorly immunogenic. Polycional antibodies were generated against bacteriaily expressed recombinant coat proteins (rCPs) of two biologically distinct AMV strains in rabbits and compared with those raised agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…SDS-PAGE analysis showed that the expression of the recombinant SCMVCp fusion protein was found to be plentiful in the total extract and in the insoluble fraction of the pellet debris of E. coli, with a molecular size of around 44 kDa, but was not presented in the supernatant as a soluble protein fraction (Figure 2A). This result is consistent with the experiments previously reported that the recombinant virus coat protein was expressed in the insoluble protein fraction [13,15]. Interestingly, the expression of the recombinant SCMVCp protein was not dose-dependent on the inducer IPTG.…”
Section: Expression and Purification Of The Recombinant Scmvcp Fusionsupporting
confidence: 93%
See 1 more Smart Citation
“…SDS-PAGE analysis showed that the expression of the recombinant SCMVCp fusion protein was found to be plentiful in the total extract and in the insoluble fraction of the pellet debris of E. coli, with a molecular size of around 44 kDa, but was not presented in the supernatant as a soluble protein fraction (Figure 2A). This result is consistent with the experiments previously reported that the recombinant virus coat protein was expressed in the insoluble protein fraction [13,15]. Interestingly, the expression of the recombinant SCMVCp protein was not dose-dependent on the inducer IPTG.…”
Section: Expression and Purification Of The Recombinant Scmvcp Fusionsupporting
confidence: 93%
“…To overcome this problem, the serological method using a polyclonal antibody against a recombinant coat protein, was commonly used in immunodiagnostics [11]. Several studies have reported on the production of polyclonal antibodies against recombinant proteins, such as the antibodies against coat protein of Pelargonium zonate spot virus [13], cucumber mosaic virus [14], or alfalfa mosaic virus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Banana streak MY virus (BSMYV) antiserum (1:2000) was used in antigen coated plate-enzyme linked immunosorbent assay (ACP-ELISA) for the detection of virus in banana plants [27]. Alfalfa mosaic virus (AMV) polyclonal antiserum was used for the detection of virus in soybean plants in USA [28]. Our results with CP are in agreement with the results obtained for antibodies raised against recombinant Watermelon bud necrosis virus [29], Potato mop-top virus [30], Potato virus Y [31], Potato virus X [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, polyclonal antibodies raised against purified virions contaminated with host tissue components, cross react with host antigens and often give variable background reactions, thus limiting their use in ELISA based diagnostic methods. Recombinant polyclonal antibodies (Pab) specific to Tomato spotted wilt virus (TSWV) [11], Potato virus Y [12], Alfalfa mosaic virus (AMV) Khatabi et al [13] have been generated and used for serological detection of cited viruses [14]. centrifuged at 12.000 rpm for 15 min.…”
Section: Introductionmentioning
confidence: 99%